PENGARUH KONSENTRASI ETANOL TERHADAP AKTIVITAS ANTIOKSIDAN EKSTRAK RIMPANG ILALANG (Imperata cylindrica (L) Beauv.) PADA EKSTRAKSI MENGGUNAKAN GELOMBANG ULTRASONIK - Suhendra, Corry Permatasari; Widarta, I Wayan Rai; Wiadnyani, Anak Agung Istri Sri (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 8 No 1 (2019): Jurnal ITEPADO - 10.24843/itepa.2019.v08.i01.p04, 2019)
This research porpose to determine the appropiate concentration of ethanol to obtain the highest antioxidant activity of cogon grass rhizome (Imperata cylindrica (Linn.) Beuv.) extract using ultrasonic wave. This research used a completely randomized design method with the treatment of concentration ethanol which consisted of six levels : 40, 50, 60,70, 80 and 90%. The whole treatment was repeated three times to obtain 18 units of the experiment. The data were analyzed by ANOVA, if the treatment showed the influenced then it continued by Duncan test . The result showed that the best treatment is using ethanol 70% with characteristic extract : yield was 14.13%, total phenolic was 129.57 mgGAE (Gallic Acid Equivalent)/g extract, total flavonoid was 90.91 mgQE (Quercetin Equivalent)/g extract and antioxidant activity was 56.03% with the IC50 value 0.098 mg/ml